TRAINING OF FUTURE TEACHER OF INFORMATICS TO WORK IN MODERN INFORMATION AND EDUCATIONAL ENVIRONMENT OF SCHOOL - Shovkun, В.В. (Journal of Information Technologies in Education (ITE), 2015)
The article analyzes the impact of new information and communication technologies in formation trends for changes in the education system. An important factor according to specific trends and satisfying the educational needs of students in the school is to create an information and communication environment (ICE). This requires the presence in educational institutions the specialists able to advise the management on the choice of hardware and software, to the design,implementation, configuration programs, serve teaching aid and others. Anonymous survey of teachers of Informatics of Kherson region is conducted and it revealed that in most cases the defined functions are performed exactly by teachers of Informatics. Only a few schools have special workers or appeal to workers or companies that provide related services. Therefore, special importance is the preparation of future teachers of Informatics for continuous tracking trends of educational technologies, self-reliant mastering of new services and applications, finding ways for their implementation in the educational process of the school, consulting colleagues, conducting explanatory work with parents. Also, in the survey we determined the level of equipment and working conditions of teachers of Informatics at school and at home.